Women's Leadership in Creating a Healthy Cultural Climate for Early Childhood Education - Edi Titik Kusnawawati (IJORER : International Journal of Recent Educational Research, 2022)
Research aims to examine and analyze the role of women in holding school leadership, especially at the Early Childhood Education Programs level. This research method analyzes studies related to women's leadership in Early Childhood Education. This type of research uses in-depth qualitative analysis. The study results show that women have an adequate ability to hold leadership in schools. Women tend to share more of their differences and are more motivated. Female principals tend to have higher teaching methods and techniques than males. In addition, it shows a more democratic nature and a more participatory style. Female principals tend to behave better and wiser than males in achieving goals. Departing from the low view and assumption of women, in the early childhood education programs world, women show many advantages in occupying the positions of Principals and Teachers compared to men, i.e., 95% are women. And the research implication is that women have more potential in the building and leading Early Childhood Education.